Suppresses of Astragalus Polysaccharide on E. coli-Induced Injured Intestinal Microvascular through TLR4-NF-κB Signal Pathways in Chickens - Su,L (2019)
ABSTRACT To investigate the hypothesis that APS can attenuate E. coli-induced microvascular dysfunction in chicken intestine, 60 0-day old male chickens were divided into three groups with 5 replications of 4 chicks. Chicken in the APS group were treated with 15 mg APS daily while the others were given 0 mg APS for 6 days. Then all 7-day old chicken were injected intraperitoneally by E. coli, except for the chicken in the control group. After 4 h, all chicken’s intestinal samples were collected to detect gene expressions involved in inflammatory factors and adhesion molecules. Results showed that APS attenuated the signs of edema and hemorrhage in 7-day old chicken intestinal mucosa which were induced by E. coli injection. Consistently, APS significantly reduced the increasing mRNA levels of inflammatory factors such as Tumor necrosis factor-a (TNF-a), interleukin (IL) -1β and inducible nitric oxide synthase (iNOS) (p<0.05), the same results were observed in vascular adhesion molecules such as E-selectin, intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1). Moreover, we observed that APS supplementation in water suppressed significantly (p<0.05) the decline of reparative factors such as epithelial growth factor (EGF) and basic fibroblast growth factor (bFGF) in E. coli injected group. Furthermore, supplementation with APS substantially blocked (p<0.05) the increase in Toll-like receptor-4 (TLR4) and Nuclear factor (NF)-κB mRNA abundance (p=0.087) induced by E. coli infection. This study indicated that microvascular injured chicken intestine induced by E. coli would be attenuated with feeding APS, and the mechanism of repairing were probably mediated through TLR4-NF-κB signal pathways.